Khalifah bin Khayyat: His "Character"and his"T1arikh" - Masoomali Panjeh (تاریخ اسلام)
The development in lslamic culture and and evolution of the science of historiography civilization is indebted to the endeavors of many historians. One such historian is the author of Khalifah bin Tarikh (History) and Tabaghat of the two books (Biographical Categories), Khayyat al-یsfuri, who is not very wellknown among the scholars and students of history of lslam. He lived in the late 2nd and early 3rd centuries AH in Basra and is considered to be a pioneer in Writing chronicles and biographical categories in Muslim historiography.works, Tarikh The article before you eximines his life and one of his major , in brief.